Transcriptional Organization and In Vivo Role of the Escherichia coli rsd Gene, Encoding the Regulator of RNA Polymerase Sigma D - Jishage, Miki (American Society for Microbiology (ASM), 1999)
The regulator of sigma D (Rsd) was identified as an RNA polymerase ς(70)-associated protein in stationary-phase Escherichia coli with the inhibitory activity of ς(70)-dependent transcription in vitro (M. Jishage and A. Ishihama, Proc. Natl. Acad. Sci. USA 95:4953–4958, 1998). Primer extension analysis of rsd mRNA indicated the presence of two promoters, ς(S)-dependent P1 and ς(70)-dependent P2 with the gearbox sequence. To get insight into the in vivo role of Rsd, the expression of a reporter gene fused to either the ς(70)- or ς(S)-dependent promoter was analyzed in the absence of Rsd or the presence of overexpressed Rsd. In the rsd null mutant, the ς(70)- and ς(S)-dependent gene expression was increased or decreased, respectively. On the other hand, the ς(70)- or ς(S)-dependent transcription was reduced or enhanced, respectively, after overexpression of Rsd. The repression of the ς(S)-dependent transcription in the rsd mutant is overcome by increased production of the ς(S) subunit. Together these observations support the prediction that Rsd is involved in replacement of the RNA polymerase ς subunit from ς(70) to ς(S) during the transition from exponential growth to the stationary phase.